The impact of match-play tennis in a hot environment on indirect markers of oxidative stress and antioxidant status - Knez, W. L; Périard, J. P. (British Journal of Sports Medicine, 2014)
Objectives The purpose of this study was to determine the impact of changes in oxidative stress and antioxidant status in response to playing tennis in HOT (~36°C and 35% relative humidity (RH)) and COOL (~22°C and 70% RH) conditions. Methods: 10 male tennis players undertook two matches for an effective playing time (ie, ball in play) of 20 min, corresponding to ~122 and ~107 min of total play in HOT and COOL conditions, respectively. Core body temperature, body mass and indirect markers of oxidative stress (diacrons reactive oxygen metabolic test) and antioxidant status (biological antioxidant potential test) were assessed immediately prematch, midmatch and postmatch, and 24 and 48 h into recovery. Results Regardless of the condition, oxidative stress remained similar throughout play and into recovery. Likewise, match-play tennis in the COOL had no impact on antioxidant status. However, antioxidants status increased significantly in the HOT compared with COOL environment (p<0.05). Body mass losses (~0.5 kg) were similar between conditions. Rectal temperature increased during both matches (p<0.05), but with a greater magnitude in the HOT (39.3±0.5°C) versus COOL (38.7±0.2°C) environment (p<0.05). Conclusions Match-play tennis in the heat does not exacerbate the development of oxidative stress, but significantly increases antioxidant status. These data suggest that the heat stress observed in the HOT environment may provide a necessary signal for the upregulation of antioxidant defence, dampening cellular damage.